1997
DOI: 10.1159/000169139
|View full text |Cite
|
Sign up to set email alerts
|

Increased Lipoproteins and Fibrinogen in Chronic Renal Allograft Dysfunction

Abstract: Chronic rejection – also called chronic renal allograft dysfunction (CRAD) – is the main cause of long-term loss of the transplanted kidney, but its pathogenesis is not well known. The aim of this study was to know if lipoproteins, fibrinogen, plasminogen activator inhibitor-1 (PAI-1) and platelet aggregation show more abnormalities in renal transplant patients with CRAD than in those with stable renal function. Sixty patients with renal allograft have been studied; 20 patients with CRAD and 40 controls matche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 8 publications
0
3
1
Order By: Relevance
“…None of the lipid parameters measured in this study appeared to be related to the effect of fluvastatin on the incidence of renal end points, which is in contrast with previous reports indicating that lipids are risk factors for renal allograft [18][19][20]30]. The commonly accepted hypothesis that lipoproteins are implicated in the pathogenesis of glomerulosclerosis is supported by the observation that patients with pretransplant hypercholesterolemia have an increased number of acute rejection episodes, worse graft function, and more graft losses during up to three years of follow-up [19].…”
Section: Discussioncontrasting
confidence: 99%
“…None of the lipid parameters measured in this study appeared to be related to the effect of fluvastatin on the incidence of renal end points, which is in contrast with previous reports indicating that lipids are risk factors for renal allograft [18][19][20]30]. The commonly accepted hypothesis that lipoproteins are implicated in the pathogenesis of glomerulosclerosis is supported by the observation that patients with pretransplant hypercholesterolemia have an increased number of acute rejection episodes, worse graft function, and more graft losses during up to three years of follow-up [19].…”
Section: Discussioncontrasting
confidence: 99%
“…Also, in a cross-sectional study, high fibrinogen levels have been associated with chronic renal allograft dysfunction (37). With regard to determinants of the fibrinolytic system, a reduction in the level of the plasma uPA level was observed in the tacrolimus group.…”
Section: Discussionmentioning
confidence: 92%
“…Posttransplant elevated lipid profiles are also associated with poor renal allograft outcomes. In addition, post-transplant hypertriglyceridemia [43,44] and fibrinogenemia [44] were independent risk factors for chronic allograft dysfunction. A more recent study showed pretransplant and post-transplant triglyceride, and lipoprotein A levels were both associated with chronic allograft dysfunction [45].…”
Section: Metabolic Diseases and Obesitymentioning
confidence: 99%